Persepsi Harga Dan Kualitas Layanan Terhadap Kepuasan Pelanggan BRT Trans Jateng Semarang–Grobogan - Vendana Argananda Wibowo; Ninik Dwi Atmini; Heru Yulianto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The purpose of this study: (1) To test and analyze the effect of price perceptions on customer satisfaction of BRT Trans Jateng. (2) Testing and analyzing service quality on BRT Trans Jateng customer satisfaction. The subjects of this study were Trans Jateng BRT (Bus Rapid Transit) consumers in 2023. This study used a quantitative approach with data collection methods using a questionnaire. The population in this study is unknown. This study used a random sampling method with a sample of 100 respondents. The data analysis method used is multiple linear regression analysis. The results showed that (1) Price perception has a positive effect on customer satisfaction for BRT Trans Central Java. (2) Service quality has a positive effect on BRT Trans Jateng customer satisfaction.